(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of this study is to investigate the preferences of Russian students in the way of learning in lectures. The paper provides an answer to the following research question: "How to teach?" students in the modern condition. The results are a real scientific fact. Statistically proven that students of the Moscow Pedagogical State University do not prefer the auditory way of learning in lectures. The result is very high statistically significant (99.9%). The result of the study may be useful at the input stage of the reform of Russian Higher Education, including for the formation of training programs for teachers.